Fiqh-Based Waste Management Model at al Utsmani Islamic Boarding School - Safira Tsaniyatur Rohaimi; Najwa Nur Hanifah; Putri Widhia Ningrum; Diah Maharani; Muhlisin Muhlisin (BAMALA Institute, 2025)
This research aims to understand the understanding of santri in pesantren management regarding the concept of environmental fiqh, waste management practices, and their relationship with sharia principles such as taharah, muamalah, and maqasid sharia. This article examines the environmental fiqh-based waste management model at Al-Utsmani Islamic Boarding School, focusing on analyzing the role and understanding of boarding school administrators in designing and implementing an independent waste management system using a qualitative case study approach. The boarding school integrates Islamic values and ecological awareness into its waste management system, which includes the structural and specific sorting, processing, and reuse of organic and inorganic waste. This system involves collaboration between students and administrators through a disciplined approach using a rotation system and educational penalties, aimed at instilling ecological character and environmental awareness. This practice not only supports environmental sustainability and character building among students, but also affirms that protecting the environment is part of the mandate and worship in Islam. The results of the study show that environmental fiqh-based waste management in Islamic boarding schools can be an effective model in building a sustainable civilization that is morally and socially r